Unilateral breast abscess due to nalidixic acid resistant salmonella enteric serovar typhi - Patel, Kinjal Prashant; Poojary, Reshma Ashwin; Parab, Sanjay Shankar; Poojary, Aruna (Indian Journal of Case Reports, 2019)
A breast abscess is a rare complication of Salmonella bacteremia; especially, in immunocompetent patients. In the era of antimicrobial resistance, untreated or resistant Salmonella can lead to abscess formation in various organs of the body. The authors report a case of unilateral breast abscess due to Nalidixic Acid Resistant Salmonella enterica serovar Typhi (NARST) in a 30-year-old immunocompetent female. This case report highlights the importance of culture & sensitivity of breast abscesses especially in patients residing in endemic areas or those with a recent history of typhoid fever.